Modulation of immune response by nanoparticle-based immunotherapy against food allergens - Krishna, Sivadas Swathi; Farhana, Syeda Ayesha; T.P., Ardra; Hussain, Shalam M.; Viswanad, Vidya; Nasr, Muhammed Hassan; Sahu, Ram Kumar; Khan, Jiyauddin (Frontiers in Immunology, 2023)
The increasing prevalence of food allergies worldwide and the subsequent life-threatening anaphylactic reactions often have sparse treatment options, providing only symptomatic relief.Great strides have been made in research and in clinics in recent years to offer novel therapies for the treatment of allergic disorders. However, current allergen immunotherapy has its own shortcomings in terms of long-term efficacy and safety, due to the local side effects and the possibility of anaphylaxis. Allergen-specific immunotherapy is an established therapy in treating allergic asthma, allergic rhinitis, and allergic conjunctivitis. It acts through the Formatted: Font: Bold, Complex Script Font: Bold Formatted: Normal downregulation of T cell-and IgE-mediated reactions, as well as desensitization, a process of food tolerance without any allergic events. This would result in a protective reaction that lasts for approximately 3 years, even after the withdrawal of therapy. Furthermore, allergen-specific immunotherapy also exploits several routes such as oral, sublingual, and epicutaneous immunotherapy. As the safety and efficacy of allergen immunotherapy are still under research, the exploration of newer routes such as intra-lymphatic immunotherapy would address unfulfilled needs. In addition, the existence of nanoparticles can be exploited immensely in allergen immunotherapy, which would lead to safer and efficacious therapy. This manuscript highlights a novel drug delivery method for allergen-specific immunotherapy that involves the administration of specific allergens to the patients in gradual increasing doses, to induce desensitization and tolerance, as well as emphasizing different routes of administration, mechanism, and the application of nanoparticles in allergen-specific immunotherapy.